2020
DOI: 10.1063/5.0014125
|View full text |Cite
|
Sign up to set email alerts
|

Switch effect for spin-valley electrons in monolayer WSe2 structures subjected to optical field and Fermi velocity barrier

Abstract: To investigate the effects of the optical field and the Fermi velocity on the transport properties of spin and valley electrons, we impose a normal/ferromagnetic/normal (N/F/N) quantum structure based on the monolayer WSe2. The results indicate that there is a strong switch effect for spin- and valley-related electrons. When left-handed off-resonant circularly polarized light is irradiated in the intermediate ferromagnetic region, 100% polarization for K valley electrons can be achieved in the entire effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…As can be seen in figure 5(a) and also is confirmed by the band structure in figure 4(c), by increasing |h|, for h > 115 meV (h < −115 meV), only spinup (-down) band permitted to pass through the barrier, leading to fully spin polarization. The polarizations behavior for θ = 0 is in agreement with previous studies on WSe 2 [13,14], confirming our theoretical model. Similarly, it is seen in figure 5(b) and also is confirmed by figure 4 As can be seen in figures 5(a) and (b), in the case of θ = 0 there is no fully spin-valley polarization.…”
Section: Photo-and Exchange-field Controlled Electron Transport At La...supporting
confidence: 92%
See 1 more Smart Citation
“…As can be seen in figure 5(a) and also is confirmed by the band structure in figure 4(c), by increasing |h|, for h > 115 meV (h < −115 meV), only spinup (-down) band permitted to pass through the barrier, leading to fully spin polarization. The polarizations behavior for θ = 0 is in agreement with previous studies on WSe 2 [13,14], confirming our theoretical model. Similarly, it is seen in figure 5(b) and also is confirmed by figure 4 As can be seen in figures 5(a) and (b), in the case of θ = 0 there is no fully spin-valley polarization.…”
Section: Photo-and Exchange-field Controlled Electron Transport At La...supporting
confidence: 92%
“…One of the promising ways to control spin and valley degrees of freedom is the use of circularly polarized light, as reported in TMDs experimentally [6][7][8][9] and theoretically [10][11][12][13][14][15][16][17][18]. This is because such light carries finite orbital angular momentum which can thus couple to the spin degree of freedom via spin-orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in order to make the approximation to regard the time-dependent Hamiltonian as time-independent, the relationship |ev F A/ℏΩ| ≪ 1 needs to hold [34,36]. In our case, light with a wavelength of 50 nm can be used (Ω = 6000 THz), which will be able to produce a band gap of ∆ Ω2 = 0.03 eV when the intensity of light is 2 × 10 16 W m −2 [28,37].…”
Section: Model and Methodsmentioning
confidence: 99%
“…Regulation of optical filed can effectively change the properties of the material [19][20][21], thereby affecting the quantum transport. At present, there have been some works exploring the modulation of light on electronic structures [22][23][24][25][26][27][28][29][30][31]. In short, the presence of light has two necessary functions in electronic systems.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that due to the adjustment of OCPL and the large spin-orbit coupling of WSe 2 , perfect valley-and spin-polarized currents are present. The group of Guo investigated the influence of OCPL and the Fermi velocity barrier on spin-and valley-polarized transport through the ML WSe 2 quantum junction [31]. The results indicate that there is a strong switch effect for spin-and valley-resolved conductance.…”
Section: Introductionmentioning
confidence: 99%